Arabin-pessary or McDonald Cerclage in Cervical Shortening? - Aytaj Jafarzade; Sveta Aghayeva; Tamer Mungan; Aydan Biri; Osman Ufuk Ekiz (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective The aim of the present study is to compare the effectiveness of Arabin pessary and McDonald cervical cerclage on preterm delivery. Methods We conducted a retrospective analysis of data from patients who underwent either Arabin pessary or McDonald cerclage between January 1, 2019, and January 1, 2023. A total of 174 patients were included in the study, with 31 undergoing Arabin pessary and 143 receiving cervical cerclage using the McDonald technique in singleton pregnant women with cervical insufficiency, which applied between 14 and 22 gestational weeks. We included singleton pregnant women with normal morphology, and with normal combined test. The primary outcome was the impact of each method on preterm delivery (< 34 gestational weeks). Results The weeks of cervical cerclage or pessary application were compatible with each other (p< 0.680). The pessary group had a statistically significant longer time to delivery compared with the Cerclage group (cerclage group mean 30.8 c 7.1 standard deviation [SD] versus pessary group mean 35.1 ± 4.4 SD; p< 0.002). A statistically significant difference was found between the pessary and cerclage groups in terms of delivery at < 34 weeks (p= 0.002). In patients with cervical length between 25 and 15mm and < 15mm, no significant difference was found between the pessary and cerclage groups in terms of delivery week (p< 0.212; p< 0.149). Regardless of the technique applied, no statistically significant difference was observed between cervical length and birth < 34 weeks. Conclusion Our study found that pessary use for cervical insufficiency is statistically more effective than cervical cerclage surgery in preventing preterm births < 34 weeks in singleton pregnancy.